2004
DOI: 10.1002/neu.20005
|View full text |Cite
|
Sign up to set email alerts
|

Survival of mammalian B104 cells following neurite transection at different locations depends on somal Ca2+ concentration

Abstract: We report that cell survival after neurite transection in a mammalian neuronal model (cultured B104 cells) critically depends on somal [Ca2+]i, a novel result that reconciles separate long-standing observations that somal survival decreases with more-proximal axonal transections and that increased somal Ca2+ is cytotoxic. Using fluorescence microscopy, we demonstrate that extracellular Ca2+ at the site of plasmalemmal transection is necessary to form a plasmalemmal barrier, and that other divalent ions (Ba2+, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(61 citation statements)
references
References 49 publications
5
55
1
Order By: Relevance
“…For a given transection distance, cells with longer PT times, up to 10 min PT, did not seal at a significantly ( p Ͼ 0.05, CMH 2 ) different frequency compared to cells with shorter PT times (Table 1). These and all other data in Table 1 confirmed that the frequency and rate of sealing in B104 cells was determined by PC time and not the time of neurite transection, as was previously reported for this and other preparations (Blanchette et al, 1999;Detrait et al, 2000b;Yoo et al, 2004). Hence, unless otherwise stated, all measures of sealing by B104 cells in this article are given in PC times.…”
Section: Pc Time Determines Plasmalemmal Sealingsupporting
confidence: 88%
See 4 more Smart Citations
“…For a given transection distance, cells with longer PT times, up to 10 min PT, did not seal at a significantly ( p Ͼ 0.05, CMH 2 ) different frequency compared to cells with shorter PT times (Table 1). These and all other data in Table 1 confirmed that the frequency and rate of sealing in B104 cells was determined by PC time and not the time of neurite transection, as was previously reported for this and other preparations (Blanchette et al, 1999;Detrait et al, 2000b;Yoo et al, 2004). Hence, unless otherwise stated, all measures of sealing by B104 cells in this article are given in PC times.…”
Section: Pc Time Determines Plasmalemmal Sealingsupporting
confidence: 88%
“…We then added 3 kDa Texas Red dextran at 0 min PC (i.e., after neurite transection) to assess sealing. As reported previously (Yoo et al, 2003(Yoo et al, , 2004Nguyen et al, 2005), cells with transected neurites identified by their relationship to the score mark were always filled with fluorescein dextran (Fig. 1 B, E), whether or not they excluded Texas Red dextran.…”
Section: B104 Cells B104 Cells Derived From a Cns Neuroblastomasupporting
confidence: 83%
See 3 more Smart Citations